Liquidity Needs and Vulnerability to Financial Underdevelopment - Raddatz, Claudio (World Bank, Washington, DC, 2014)
The author provides evidence of a causal and economically important effect of financial development on volatility. In contrast to the existing literature, the identification strategy is based on the differences in sensitivities to financial conditions across industries. The results show that sectors with larger liquidity needs are more volatile and experience deeper crises in financially underdeveloped countries. At the macroeconomic level, the results suggest that changes in financial development can generate important differences in aggregate volatility. The author also finds that financially underdeveloped countries partially protect themselves from volatility by concentrating less output in sectors with large liquidity needs. Nevertheless, this insulation mechanism seems to be insufficient to reverse the effects of financial underdevelopment on within-sector volatility. Finally, the author provides new evidence that: 1) Financial development affects volatility mainly through the intensive margin (output per firm). 2) Both the quality of information generated by firms, and the development of financial intermediaries have independent effects on sectoral volatility. 3) The development of financial intermediaries is more important than the development of equity markets for the reduction of volatility.